The Value of Independence in Storybooks “Aku Sudah Besar” by Futri Wijayanti - Mujiati, Sri (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Independence is the ability of individuals to carry out various activities independently without requiring assistance from others. The purpose of this study is to describe how the process of children's independence consists of motor aspects, social aspects, and emotional aspects in the Aku Sudah Besar Storybook. Quantitative research design with content analysis technique The results showed that there is a value of independence in the book Aku Sudah Besar which consists of motor aspects in the form of physical motor development shown in the explanation of the child's feet and hands experiencing greater changes than before. The ability to wear their own clothes, and the ability to bathe alone. Social aspects are shown in the explanation of Sympathy, Empathy, Social Support, Sharing, Familiar behavior. and emotional aspects are shown in the explanation of curiosity and affection for his sister.